2019
DOI: 10.3389/fpsyg.2019.00174
|View full text |Cite
|
Sign up to set email alerts
|

Improving Cognitive Performance of 9–12 Years Old Children: Just Dance? A Randomized Controlled Trial

Abstract: Exercise is assumed to have positive effects on children’s cognitive performance. However, given the inconclusive evidence for the long-term effects of exercise, it is difficult to advice schools on what specific exercise programs can improve children’s cognitive performance. In particular, little is known about the effects of small exercise programs that may be feasible in daily school practice. Therefore, we assessed the effects of a 9-weeks program consisting of daily exercise breaks on children’s cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 79 publications
(112 reference statements)
3
38
0
Order By: Relevance
“…In the present study, we found that children who performed two 5-min CABs in a typical school day, spent about 6 min less time in sedentary behavior and increased their light and MVPA (of about 4 and 2 min) with respect to controls. Our findings show the effectiveness of AulAttiva in increasing time dedicated to PA along the school day in the real world, in agreement with other similar studies [ 24 , 25 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we found that children who performed two 5-min CABs in a typical school day, spent about 6 min less time in sedentary behavior and increased their light and MVPA (of about 4 and 2 min) with respect to controls. Our findings show the effectiveness of AulAttiva in increasing time dedicated to PA along the school day in the real world, in agreement with other similar studies [ 24 , 25 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…Apart from Powerpoint, respondents were also given material through the snake and ladder game. The use of snakes and ladders in this study contains elements of play and aims in order to encourage respondents to learn about what they did in the game (Berg et al, 2019). Which refers to our findings, this further strengthens the participants' efforts in capturing the health education material we imply.…”
Section: Discussionsupporting
confidence: 70%
“…Meanwhile, one of the health education methods that we would like to highlight here is a method that uses the snake and ladder playing technique. In the previous research which directed, the game of snakes and ladders has been proven to transform a passive learning atmosphere to become active and children become cheerful, which makes them able to capture more information (Berg et al, 2019). This learning technique has been used so that learning objectives can be achieved effectively and efficiently in a happy atmosphere even though discussing difficult things (Raiyn, 2017;Sites, 2016).…”
mentioning
confidence: 99%
“…Despite these limitations, this pilot and feasibility study was useful to test how to implement this type of intervention in the school setting. The results encourage us to implement the protocol with a structured study involving a larger sample of children and teachers, and investigating other aspects, in particular the effects of ABs on cognitive functions and quality of life [47,48].…”
Section: Discussionmentioning
confidence: 88%